2011
DOI: 10.1002/anie.201101654
|View full text |Cite
|
Sign up to set email alerts
|

Allylic CH Alkylation of Unactivated α‐Olefins: Serial Ligand Catalysis Resumed

Abstract: A delicate interplay of several kinetically labile ligands is required for reactions that proceed through serial ligand catalysis mechanisms. An investigation of the disruption of this balance has enabled the development of a method for the intermolecular allylic CH alkylation of unactivated as well as activated α‐olefins (see example, Bn=benzyl).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
36
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 138 publications
(37 citation statements)
references
References 50 publications
1
36
0
Order By: Relevance
“…The predominance of unbound Pd(OAc) 2 in the presence of PhS(O)C 2 H 4 S(O)Ph has also been observed experimentally. 56,57 In contrast, the Pd(OAc) 2 /4,5-diazafluorenone complex is exergonic by 4.2 kcal/mol with respect to unbound Pd(OAc) 2 , indicating that the latter is not the resting state in this catalytic system (see the Supplementary Information for details). We also considered the involvement of a Lewis base-coordinated Pd-π-allyl species in these studies of theoretical binding affinities (see the Supplementary Information for further details).…”
Section: Resultsmentioning
confidence: 99%
“…The predominance of unbound Pd(OAc) 2 in the presence of PhS(O)C 2 H 4 S(O)Ph has also been observed experimentally. 56,57 In contrast, the Pd(OAc) 2 /4,5-diazafluorenone complex is exergonic by 4.2 kcal/mol with respect to unbound Pd(OAc) 2 , indicating that the latter is not the resting state in this catalytic system (see the Supplementary Information for details). We also considered the involvement of a Lewis base-coordinated Pd-π-allyl species in these studies of theoretical binding affinities (see the Supplementary Information for further details).…”
Section: Resultsmentioning
confidence: 99%
“…Within recent years, our laboratory has introduced electrophilic Pd(II)/sulfoxide catalysis as a general platform for allylic C–H activation that enables direct allylic esterification, 12 amination, 13 and alkylation 14 of terminal olefins through the intermediacy of a π-allylPd species. We hypothesized that a dehydrogenation reaction of terminal olefins could also be developed using this reaction manifold by promoting β-hydride elimination from the π-allylPd intermediate, in the absence of nucleophile.…”
mentioning
confidence: 99%
“…18 While the use of Pd(OAc) 2 resulted in only recovered starting material (entry 1), Pd(II)/phenylbis-sulfoxide catalyst 1 provided initial dehydrogenation reactivity, albeit in low yield (6% yield of 3a , entry 2). After a survey of ligands, it was found that 10 mol% of the Pd(II)/benzylbis-sulfoxide catalyst 2 12a,14b,14c resulted in higher catalytic turnover, leading to 28% diene product (4:1 E:Z selectivity, entry 3). Longer reaction times led to significantly diminished yields, indicating that the 1,3-butadiene product was not stable to the reaction conditions.…”
mentioning
confidence: 99%
“…3,4 Unfortunately, C–H alkylation methods have been limited in scope to disubstituted methylene nucleophiles bearing two electron-withdrawing groups (Scheme 1A). Previous reports employing tertiary nucleophiles in allylic C–H alkylation reactions have been limited with respect to either olefin scope (i.e., only 1,4-dienes) or nucleophile scope (i.e., tetralones) (Scheme 1B).…”
Section: Introductionmentioning
confidence: 99%